Internet abuse: offensive propaganda on social media / Mohd Elmi Izha Md Alui - Md Alui, Mohd Elmi Izha (2014)
Social media plays an important role today with information that can be accessed in a very fast way. In this scenario, the social media now are being abused by some people who use the platform as a sphere of propaganda to poison the brains of the people through propaganda. This is an investigative research that focus on Malaysian views on offensive propaganda in social media and IT enforcement policy to control on issues in social media. To collect all the relevant data, there are two methods that being applied, first is by doing some reading on the several articles and journals related to the topic. The other method is conducting an interview with relevant participant and observation. The result highlights that Malaysian now are aware of the offensive propaganda in social media and it's manageable and can be controlled by law enforcement agencies in the future. The significance of this study is useful to government and society as a preliminary interpretation of the relevant phenomena occurring propaganda offensive in the country and some of the steps are being taken government agencies to curb on it. Even though this research has successfully met the target, but for future work it will urge to supply large scale of people's ideas and holistic cyber law enforcement policy from time to time.